(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
In today’s digital age, Legal practitioners heavily depend on online legal information resources to enhance legal research and support legal activities. However, it has been observed that many legal practitioners lack effective information retrieval skills to efficiently navigate and extract relevant information through these information resources. This study therefore examined the influence of information retrieval skills on the use of online legal resources among legal practitioners in Ogun State. The study adopted a survey research method with questionnaire as the instrument of data collection. The study population consist of 699 legal practitioners drawn from all the five branches of Nigeria Bar Association in Ogun State. The sample size was determined using Krejcie and Morgan table which resulted in a sample of 242. The data collected was analysed using both descriptive and inferential statistics. The study found that the level of use of online legal information resources (mean=2.63) information retrieval skills (mean = 2.56) is moderately high among the respondents. The test of hypothesis showed that information retrieval (Adj.R2 = 0.528 p = 0.000) has significant influence on the use of online legal information resources. The study concluded that the use of online legal resources by legal practitioners will provide extensive access to legal materials which will in turn promote quick dispensation of justice and enhance lawyer’s productivity. It therefore recommended the need for comprehensive training programs and continuing education by the law libraries to enhance lawyers’ information retrieval skills.